2011
DOI: 10.1088/0004-637x/736/1/13
|View full text |Cite
|
Sign up to set email alerts
|

THE PHOTOEVAPORATIVE WIND FROM THE DISK OF TW Hya

Abstract: Received; accepted suggest that most of the emitting gas traced at optical wavelengths is bound to the system rather than unbound. We discuss the implications of our results for a planet-induced versus a photoevaporation-induced gap.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
121
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(135 citation statements)
references
References 68 publications
14
121
0
Order By: Relevance
“…This is not surprising given TW Hya near face-on inclination and the fact that the [OI]6300 line is emitted from the very inner regions of the disc wind , where the underlying disc is devoid of dust, allowing us to see the redshifted outflowing gas. The 10 km/s FWHM and ∼ 10 −5 L line luminosity measured by Pascucci et al (2011) for [OI]6300 are also well reproduced by the X-ray photoevaporation models presented by Ercolano & Owen (2016) for accretion and X-ray luminosities and the inclination of TW Hya. (2007) found that large grains disappear quickly (10 4 yr) from the inner disc due to radial drift, suggesting that a gap would turn quickly into a hole, with no detectable central point source.…”
Section: Evidence Of X-ray Photoevaporation In Tw Hyasupporting
confidence: 66%
See 1 more Smart Citation
“…This is not surprising given TW Hya near face-on inclination and the fact that the [OI]6300 line is emitted from the very inner regions of the disc wind , where the underlying disc is devoid of dust, allowing us to see the redshifted outflowing gas. The 10 km/s FWHM and ∼ 10 −5 L line luminosity measured by Pascucci et al (2011) for [OI]6300 are also well reproduced by the X-ray photoevaporation models presented by Ercolano & Owen (2016) for accretion and X-ray luminosities and the inclination of TW Hya. (2007) found that large grains disappear quickly (10 4 yr) from the inner disc due to radial drift, suggesting that a gap would turn quickly into a hole, with no detectable central point source.…”
Section: Evidence Of X-ray Photoevaporation In Tw Hyasupporting
confidence: 66%
“…The [OI]6300 has also been shown to be produced in a slow-moving quasi-neutral X-ray photoevaporative wind (Ercolano & Owen, 2016), and is often observed to be blue-shifted with a low-velocity component of a few km/s. In the case of TW Hya the [OI]6300 was found to be centred on the stello-centric velocity (Pascucci et al 2011). This is not surprising given TW Hya near face-on inclination and the fact that the [OI]6300 line is emitted from the very inner regions of the disc wind , where the underlying disc is devoid of dust, allowing us to see the redshifted outflowing gas.…”
Section: Evidence Of X-ray Photoevaporation In Tw Hyamentioning
confidence: 99%
“…These results all suggest that photoevaporation plays a dominant role in disk evolution at late times. This theoretical view is supported by recent observations of blue-shifted forbidden emission lines from some T Tauri stars (Pascucci and Sterzik, 2009;Pascucci et al, 2011). These observations unambiguously detect a slow (∼ 10 km/s), ionized wind, and are broadly consistent with the predictions of photoevaporation models (Alexander, 2008b;Ercolano and Owen, 2010); further such data will provide important new insight into the processes driving disk clearing.…”
Section: Importance Of Photoevaporation In Disk Evolutionsupporting
confidence: 75%
“…5 presents a compilation of the Hα line profiles for our class II and class III sources). The errors on the EWs and fluxes were computed using a Monte Carlo approach: we added a normally distributed noise to the spectrum, following the error at each wavelength, and gave as error the standard deviation of the EW distribution of 1000 such spectra (Pascucci et al 2011). The errors on the flux determination are larger for the fainter lines, as the continuum calibration around these lines is more uncertain.…”
Section: Emission Lines As Accretion Diagnosticsmentioning
confidence: 99%